Swine market prospects - Kropf, J.; McCoy, J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Prices for market barrows and gilts began a significant upward trend in July, 1974. By spring of 1975 hog feeding profits had improved substantially over a year earlier. Improved profits would be expected to lead to expanded production. The Hogs and Pigs Report for 14 states released September 19, 1975 by the Statistical Reporting Service indicated sow farrowing intentions for September-November are down 7 percent. While December-February farrowing intentions are up 6 percent, the resulting increased pork production available by mid-year should not significantly affect prices.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Market prospects; Production; Farrowing